Nonlinear dynamics of livestock assets: Evidence from Ethiopia - Van Campenhout, Bjorn; Dercon, Stefan (International Food Policy Research Institute, 2012)
Recent research on the intertemporal dynamics of poverty using microeconomic data often hints at the existence of poverty traps, where some find themselves trapped at a low-level stable equilibrium while others enjoy a higher stable equilibrium. Without a sizable positive shock to well-being, those trapped at the low equilibrium will not automatically outgrow destitution, but merely fluctuate around that low-level equilibrium. Given the dramatic policy consequences implied by such a theory, knowledge about the location of the different equilibria would be extremely helpful. In this paper, we explore the possibilities of threshold-type models to identify those crucial parameters. We illustrate the method by searching for traps in the dynamics of livestock asset holdings in rural Ethiopia. We find evidence of distribution-dependent dynamics and multiple equilibria for tropical livestock units.